Pengaruh Penerimaan Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan Bermotor terhadap Pendapatan Asli Daerah untuk Pembangunan di Kabupaten Brebes Tahun 2008-2017 (Studi Empiris pada BPPKAD Kabupaten Brebes) - Tuti Alawiyah; Maftukhin; Andi Yulianto; Anisa Sains Kharisma; Yenny Ernitawati (Universitas Muhadi Setiabudi, 2019)
This research was conducted at the Regional Financial and Asset Management Revenue Agency (BPKAD) of Brebes Regency. This study was conducted to determine the variables of motor vehicle tax and motor vehicle name return duties which have a partial or simultaneous effect on local original income. This research was conducted at the BPKAD office, Brebes Regency during the period 2008-2017. Based on the statistical results, the value of the motor vehicle tax calculation (X1) of 5,544 is greater than the ttabel of 2,365 this result shows that the motor vehicle tax affects the original income of the region. The calculated value of motor vehicle name reversal duty (X2) 1.298 is smaller than the 2.365 result shows that the motor vehicle name reversal duty has no effect on the original income of the region. Then the calculated F value of 43,179 is greater than F table 4.46 indicates that there is a simultaneous effect of motor vehicle tax and motor vehicle name duty on the original income of the county. Based on the Determination test, it shows a figure of 0.925. These results show that the effect of motor vehicle tax and motor vehicle name duty on local revenue is 92.5%.